Kredibilitas Kepolisian Negara Republik Indonesia di Mata Mahasiswa - Ahmad Khumaedi; Slamet Mulyana; Teddy Kurnia Wirakusumah (Pusat Riset dan Inovasi Nasional, 2024)
Nowaday there is widespread coverage in the mass media regarding one of the institutions tasked with enforcing the law in the country of Indonesia related to cases of law violations committed by its own members, namely the Indonesian National Police. The police whose duty is to protect, protect and serve the community in carrying out their work must be directed to the community they serve so that their work can run well. However, the fact is that there are many cases of law violations committed by unscrupulous members of the police as well as the abuse of the functions and duties of the Police which have been regulated in the law which directly tarnishes the name of the Police tasked with protecting, nurturing and serving the community. Purpose: This research aims to determine the level of trustworthiness, expertise, and attractiveness of the Police in the eyes of students. Method: The method in this study is a quantitative descriptive methods. The data uses primary data through the distribution of questionnaires and literature studies such as books, journals and literature sources. Results: There are three aspects examined in source credibility, namely trustworthiness, expertise and attractiveness. The interval scale of the trustworthiness aspect is at a low level of trust where the dominant respondent who answered 54.72%. A total of 51.18% of respondents considered that the expertise aspect fell into a high category.. Regarding the attractiveness aspect of Polri, 61.02% of respondents considered that this aspect of Polri's attractiveness was in the moderate category.